2004
DOI: 10.1590/s1984-63982004000100015
|View full text |Cite
|
Sign up to set email alerts
|

Feedback to grammar mistakes in EFL classes: a case study

Abstract: Este artigo reporta a análise da correção de erros gramaticais de duas turmas de inglês como língua estrangeira (LE) e como os alunos avaliam esse tipo de correção. Os dados são provenientes de transcrições de dez aulas de dois grupos de alunos de nível pré-intermediário, totalizando 7,5 horas de observação em cada grupo. A mesma professora lecionava para os dois grupos analisados e através de um questionário respondido pelos alunos foi possível observar as suas crenças com relação aos procedimentos de correçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Hammond (1995, as cited in Rauber & Gil, 2004) pointed out that with the decline of the audio lingual method in the 1960s and 1970s and the popularity of communicative language teaching since then, less attention was given to the production of accurate output by EFL learners. The focus in EFL classes shifted, in the 1970s, to the ability to communicate, and form was believed to be acquired through learners' constant exposure to comprehensible input.…”
Section: The Role Of Interaction Corrective Feedback and Noticing Inmentioning
confidence: 99%
“…Hammond (1995, as cited in Rauber & Gil, 2004) pointed out that with the decline of the audio lingual method in the 1960s and 1970s and the popularity of communicative language teaching since then, less attention was given to the production of accurate output by EFL learners. The focus in EFL classes shifted, in the 1970s, to the ability to communicate, and form was believed to be acquired through learners' constant exposure to comprehensible input.…”
Section: The Role Of Interaction Corrective Feedback and Noticing Inmentioning
confidence: 99%
“…Explicit spelling instruction: Providing students with explicit instruction on spelling rules, patterns, and strategies can enhance their spelling competence Cañado, M. (2006). A study by Rauber & Gil (2004) highlights the benefits of explicit instruction in English spelling. The research, which involved a pre-test, post-test, and delayed post-test control group design, demonstrated that drawing students' conscious attention to various spelling dimensions significantly improved their performance.…”
Section: Language-specific Challengesmentioning
confidence: 99%
“…While some researches use the label negative feedback to indicate this grammar option (ELLIS, 1995;ELLIS, 1998ELLIS, , 1999LONG, 1977;LONG, INAGAKI and ORTEGA, 1998), others prefer the term corrective feedback (NASSAJI and SWAIN, 2000;LYSTER and RANTA, 1997). Also, some recent researches have been using just feedback (RAUBER and GIL, 2004;CUNHA and LIMA, 2002;KOWAL and SWAIN 1994). The first term could…”
Section: Negative Feedbackmentioning
confidence: 99%